Pengembangan Nilai Moral Anak Usia Dini melalui Metode Keteladanan di PAUD Kota Langsa - Rafidhah Hanum; Irwandi Irwandi (Institut Agama Islam Negeri Padangsidimpuan, 2022)
The problem in this study is that there are children who have good moral values and the learning of moral values carried out by teachers is already applicable to students. This research was conducted to find out how the implementation of the development of moral values in early childhood aged 4-5 years through the exemplary method in PAUD Thursina and PAUD Al-Faiz Langsa City. This research uses a qualitative research type. The subject of this research is the classroom teacher. The informants of this study were the principal, class assistant teacher. The method used in this research is observation, documentation and interviews. The results of this study indicate that in general the development of moral values for children aged 4-5 years in Al Faiz PAUD and Thursnina PAUD Langsa City has been carried out well. The implementation is carried out using various learning methods and techniques, parental involvement, moral value development strategies and in the implementation of KBM. While evaluation in the development of moral values is carried out by means of assessment, but in its implementation there is no specific assessment, but joins in all fields. Supporting factors in the implementation of the development of moral values in PAUD Al Faiz and PAUD Thursnina include: 1) the existence of workshops for educators in developing religious and moral values, 2) the existence of habituation boards and advice boards on moral values, 3) the existence of learning facilities and infrastructure adequate. While the inhibiting factors in the development of moral values in PAUD Al Faiz and PAUD Thursnina include: 1) differences in parenting patterns for students, 2) lack of cooperation from parents of students, 3) limited learning time, 4) differences in children's ability to follow learning